Hospital Information Systems in the Ghanaian Psychiatric Hospitals: Post Act 846 of 2012 Review Analysis - Marful, Welborn Amaoko; Winter, Alfred (Journal of Health Informatics in Africa, 2018)
Introduction: Information systems are expected to exist in every hospital in almost every country to offer a systematic process of collecting appropriate records for health service delivery at all levels. This holds at least for non-computer-based information systems. Quality healthcare by hospitals depends mostly on well-organised data for accuracy, timeliness and completeness and representativeness.Objective: This study assessed existing the existing information system scenarios in psychiatric hospitals in Ghana since the passage of the Act 846 of 2012 which aims to transform the psychiatric health system in Ghana.Methods: The authority responsible for psychiatric health in Ghana was contacted for access to the three psychiatric hospitals to arrange interviews and document reviews. The study used structured interviews to gather information from the psychiatric hospitals’ directors, hospital administrators, records officers, additional staff each from hospitals for analysis.Results and Conclusions: The analysis suggests the presence of independent information systems in these hospitals which are manual-based systems. The various systems in the hospitals have been in existence for years with no knowledge of migrating to computer-based hospital information systems. The analysis further suggests the need for a trans-institutional computer-based information system to improve psychiatric service delivery and to ease information exchange for management decisions and policies.Keywords: Hospital Information System (HIS), Information System (IS), Information Management (IM), Information Technology (IT), Trans-institutional health information systems (tHIS), Psychiatric, Ghana.